Evolution of tourism in East Africa (1900-2000) - Ouma, Joseph P. B. M. (Nairobi : East African Literature Bureau, 1970)
The book is primarily a geographical text explaining the evolution of tourism in East Africa
Bibliography: p. [114]-117.
II 15/01/2019
Loans
Keywords: Tourism